2019
DOI: 10.1108/ijlma-04-2018-0062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the busyness and board independence on the discretionary disclosures of Indian firms

Abstract: Purpose The purpose of this paper is to empirically investigate the impact of board characteristics such as size, independence, busyness and duality on the extent of discretionary disclosures of listed Indian firms. Design/methodology/approach A disclosure index with 110 items was constructed to assess the discretionary disclosures in the annual reports of listed firms. The study measured disclosure using 1,024 firm-year observations over 8 years from 2009 to 2016. Board characteristics such as size, indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…This paper studies six mechanisms of board composition (board size, board independence, board financial expertise, board busyness, CEO duality, and board gender diversity) in order to explore their impact on information asymmetry. Board size (BoDS) is defined as the aggregate number of members on the board [ 102 ]; board independence (BINED) is defined as the total number of independent directors to the total number of directors on the board [ [103] , [104] ] ; board financial expertise (BFE) is defined as the total number of directors with accounting and finance degrees to the total number of directors on the board [ 62 , 105 ]; board busyness (BBusy) is described as the number of directors that serve on two or above boards to the total aggregate number of board directors [ 106 ]; CEO duality (CEOD) is measured by a dummy variable, which takes 1 if the CEO and the chairman are the same person and 0 otherwise [ 75 ]; and board gender diversity (BDG) is measured as the number of female directors to the total aggregate number of board directors [ 91 , 87 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper studies six mechanisms of board composition (board size, board independence, board financial expertise, board busyness, CEO duality, and board gender diversity) in order to explore their impact on information asymmetry. Board size (BoDS) is defined as the aggregate number of members on the board [ 102 ]; board independence (BINED) is defined as the total number of independent directors to the total number of directors on the board [ [103] , [104] ] ; board financial expertise (BFE) is defined as the total number of directors with accounting and finance degrees to the total number of directors on the board [ 62 , 105 ]; board busyness (BBusy) is described as the number of directors that serve on two or above boards to the total aggregate number of board directors [ 106 ]; CEO duality (CEOD) is measured by a dummy variable, which takes 1 if the CEO and the chairman are the same person and 0 otherwise [ 75 ]; and board gender diversity (BDG) is measured as the number of female directors to the total aggregate number of board directors [ 91 , 87 ].…”
Section: Methodsmentioning
confidence: 99%
“…The chairman and the CEO are considered to be the crucial leaders of corporations. The chairman is responsible for addressing strategic matters, setting agendas, leading the meetings of the board, representing the firm in front of other outside corporations, etc., whereas the CEO is responsible for managing the corporation and its daily operational responsibilities [ 75 ]. Normally, the posts of the chairman and CEO are held by two different individuals; however, it is not uncommon to find corporations where one individual holds the dual role of chairman and CEO of the board (referred to as duality).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Field, Lowry, and Mkrtchyan (2013) found a positve and significant relationship between busy board of directors and company value. Kavitha et al (2019) investigated the effect of busy board of directors on discretionary disclosures among 500 companies listed in India. They found that busy board of directors has negative impact on discretionary disclosures.…”
Section: Activities Of Board Of Directorsmentioning
confidence: 99%
“…58 Kavitha et al (2018) Discretionary disclosures is positively influenced by independent directors but negatively by boards with duality and the busyness of the director 59 Chauhan and Kumar (2017) Female directors face more attendance problems compared to male directors, and are less likely to be employed in monitoring-related committees. 73 Chahal and Kumari (2013) Boardroom characteristics have an insignificant impact on business performance, while audit committee and ownership structure have a significant impact on business performance.…”
mentioning
confidence: 99%